A Genetic Locus in Elizabethkingia anophelis Associated with Elevated Vancomycin Resistance and Multiple Antibiotic Reduced Susceptibility - William L. Johnson; Sushim Kumar Gupta; Suman Maharjan; Randy M. Morgenstein; Ainsley C. Nicholson; John R. McQuiston; John E. Gustafson (Antibiotics, 2024)
The Gram-negative Elizabethkingia express multiple antibiotic resistance and cause severe opportunistic infections. Vancomycin is commonly used to treat Gram-positive infections and has also been used to treat Elizabethkingia infections, even though Gram-negative organisms possess a vancomycin permeability barrier. Elizabethkingia anophelis appeared relatively vancomycin-susceptible and challenge with this drug led to morphological changes indicating cell lysis. In stark contrast, vancomycin growth challenge revealed that E. anophelis populations refractory to vancomycin emerged. In addition, E. anophelis vancomycin-selected mutants arose at high frequencies and demonstrated elevated vancomycin resistance and reduced susceptibility to other antimicrobials. All mutants possessed a SNP in a gene (vsr1 = vancomycin-susceptibility regulator 1) encoding a PadR family transcriptional regulator located in the putative operon vsr1-ORF551, which is conserved in other Elizabethkingia spp as well. This is the first report linking a padR homologue (vsr1) to antimicrobial resistance in a Gram-negative organism. We provide evidence to support that vsr1 acts as a negative regulator of vsr1-ORF551 and that vsr1-ORF551 upregulation is observed in vancomycin-selected mutants. Vancomycin-selected mutants also demonstrated reduced cell length indicating that cell wall synthesis is affected. ORF551 is a membrane-spanning protein with a small phage shock protein conserved domain. We hypothesize that since vancomycin-resistance is a function of membrane permeability in Gram-negative organisms, it is likely that the antimicrobial resistance mechanism in the vancomycin-selected mutants involves altered drug permeability.